The state of knowledge on technologies and their use for fall detection: A scoping review - Cruz, Antonio miguel; Rios Rincon, Adriana Maria; Lili, Liu; Lapierre, Nolween; Neubauer, Noelanahh; Rousseau, Jacqueline (Elsevier, 2018)
Globally, populations are aging with increasing life spans. The normal aging process and the resulting disabilities increase fall risks. Falls are an important cause of injury, loss of independence and institutionalization. Technologies have been developed to detect falls and reduce their consequences but their use and impact on quality of life remain debatable. Reviews on fall detection technologies exist but are not extensive. A comprehensive literature review on the state of knowledge of fall detection technologies can inform research, practice, and user adoption.

En todo el mundo, la población envejece con una duración de vida cada vez mayor. El proceso normal de envejecimiento y las discapacidades resultantes aumentan el riesgo de caídas. Las caídas son una causa importante de lesiones, pérdida de independencia e institucionalización. Se han desarrollado tecnologías para detectar las caídas y reducir sus consecuencias, pero su uso e impacto en la calidad de vida siguen siendo discutibles. Existen revisiones sobre las tecnologías de detección de caídas, pero no son extensas. Una revisión bibliográfica exhaustiva sobre el estado de los conocimientos de las tecnologías de detección de caídas puede servir de base para la investigación, la práctica y la adopción por parte de los usuarios.
Keywords: Tecnología; Adultos mayores; Caídas (Accidentes) en la vejez; Falls (Accidents) in old age; Scoping review; Falls; Technology; Older adults; Revisión de alcance; Caídas; Tecnología; Adultos mayores